2009
DOI: 10.1136/jnnp.2009.173740
|View full text |Cite
|
Sign up to set email alerts
|

The instrumented timed up and go test: potential outcome measure for disease modifying therapies in Parkinson's disease

Abstract: The Timed Up and Go (TUG) test has been used to assess balance and mobility in Parkinson’s Disease (PD). However, it is not known if this test is sensitive to subtle abnormalities present in early stages of the disease, when balance and gait problems are not clinically evident but may be detected with instrumented analysis of movement. We hypothesize that postural transitions and arm swing during gait will be the most sensitive characteristics of the TUG for early PD. In the present study, we instrumented the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
259
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(300 citation statements)
references
References 42 publications
16
259
1
6
Order By: Relevance
“…Based on algorithms described elsewhere [18][19][28][29], different parameters of gait and postural transition during iTUG performance were measured.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on algorithms described elsewhere [18][19][28][29], different parameters of gait and postural transition during iTUG performance were measured.…”
Section: Discussionmentioning
confidence: 99%
“…A normalization of the arm swing on the affected side might be a parameter for recovery of normal gait. Zampieri et al identified the iTUG parameter "peak arm swing velocity" as one of the most sensitive deficits in early PD [19]. It might be that the parameter "arm swing" is also of clinical relevance poststroke.…”
Section: Wüest Et Al Sensor-based Itug Reliability and Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…For fall-risk assessment, an instrumented TUG test that uses portable inertial sensors (iTUG test) has been proposed to improve the TUG test in several ways; namely, by allowing for automatic detection and separation of each performance, facilitating a detailed analysis of each and enabling a higher sensitivity than the TUG test [21,[24][25][26]. Sensitive and reliable measures for fall-risk assessment have been provided by measurement of wearable inertial sensors [27].…”
Section: Discussionmentioning
confidence: 99%